Mediación obligatoria como requisito previo al inicio de un proceso judicial. - Copara Teca, Edwin Vinicio (2023)
Since the appearance of the human being, they have been immersed in multiple types of conflicts, due to the search for the satisfaction of their needs; These disagreements are considered natural in social coexistence. The lack of communication generates disagreements and it is the parties in conflict who must directly seek a solution, deposing positions and perceptions about people and focusing their direct attention on the problem. One of the challenges of Human Rights in the 21st century is to achieve a society where a culture of peace and freedom becomes effective. For this, it has urged the States to look for new ways to solve problems and manage a conflict, which is being done through alternative methods of conflict resolution.